Nuclear and Nucleolar Image Analysis of Human Breast Epithelial Cells Transformed by benzo[a]pyrene and Transfected with the c-Ha-ras oncogene - Luís Fernando Barbisan; Jose Russo; Maria Luiza S. Mello (Analytical Cellular Pathology)
Changes in nuclear and nucleolar morphometric parameters were investigated by image analysis procedures in human breast MCF-10F epithelial cells expressing different stages of the tumourigenic progression after benzo[a]pyrene (BP) transformation (BP1, BP1-E, and BP1-E1 cell lines), and additionally transfected with the c-Ha-ras oncogene (BP1-Tras cell line). Nuclear pleomorphism was evident in all the transformed cells. The analysis of different morphometric parameters did not show a clear relationship between specific nuclear and nucleolar changes and the expression of the different stages of the tumourigenesis, with the exception of the nucleolar size, which could be associated to the expression of the tumourigenic phenotype, and a nucleolar area/nuclear area ratio, which discriminated the immortalized, the transformed, and the tumourigenic phenotypes from one another. The nuclear morphometric data established for the BP-transformed cells and for the cells additionally transfected with the c-Ha-ras oncogene were suggestive of complex and distinct morphofunctional mechanisms involving the in vitro transformation of the MCF-10F cells. The nuclear changes found in the BP1-Tras cell line were assumed to be related to the additional effects and/or enhanced genomic instability induced by transfection with the ras oncogene.